2016
DOI: 10.1097/md.0000000000004160
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative aspartate aminotransferase to platelet ratio index change predicts prognosis for hepatocellular carcinoma

Abstract: An elevated preoperative aspartate aminotransferase (AST) to platelet ratio index (APRI) is reported to be a prognostic factor for patients with hepatocellular carcinoma (HCC) after treatment. However, delta APRI (ΔAPRI), which represents the change from preoperative to postoperative APRI, has received little attention. The present study was designed to evaluate the prognostic value of ΔAPRI in patients with small HCC after liver resection.A retrospective cohort study analyzing 244 patients with small HCC who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Studies have suggested that APRI has a strong correlation with liver histopathological findings. As liver fibrosis and cirrhosis are crucial factors for development of HCC, APRI had also been reported to be as an independent prognostic factor in HCC patients with curative resection and radiofrequency ablation 29. Combining NLR and APRI may improve the prognostic accuracy in HCC patients after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that APRI has a strong correlation with liver histopathological findings. As liver fibrosis and cirrhosis are crucial factors for development of HCC, APRI had also been reported to be as an independent prognostic factor in HCC patients with curative resection and radiofrequency ablation 29. Combining NLR and APRI may improve the prognostic accuracy in HCC patients after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, thrombocytopenia is common in HCC patients and may be explained by portal hypertension leading to pooling of platelets in an enlarged spleen, typically associated with cirrhosis [ 3 ]. Many studies [ 27 , 28 ] have identified platelet involvement in inflammatory responses, liver regeneration, and the regulation of angiogenesis, with additional studies demonstrating that platelet count and platelet-based models represent effective tools for the prediction of postoperative HCC recurrence, particularly late recurrence. Consequently, the fibrosis-4 model offers the potential ability to influence prognosis of HCC patients and represents a potential independent prognostic factor for both overall survival and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several serum markers that can be used as noninvasive tools have been identified in human cancers, including HCC (Lin et al, 2017) among them, there has been great interest in the aspartate aminotransferase-to-platelet ratio index (APRI) because it is an inexpensive and feasible test that can be used for daily oncologic practice. It has been reported that APRI might be a candidate as a prognostic biomarker in HCC and in cases of cirrhosis pre-HCC (Peng et al, 2016).…”
Section: -Aspartate Aminotransferase-to-platelet Ratio Index (Apri)mentioning
confidence: 99%